Impaired cardiac pumping function and increased afterload as determinants of early hemodynamic alterations in Cushing disease - Agnieszka Włochacz; Paweł Krzesiński; Beata Uziębło-Życzkowska; Przemysław Witek; Grzegorz Zieliński; Anna Kazimierczak; Robert Wierzbowski; Małgorzata Banak; Grzegorz Gielerak (Scientific Reports)
Abstract The long-term hypercortisolemia of Cushing disease (CD) may lead to hemodynamic disorders by increasing subclinical cardiac and vascular dysfunction. The purpose of this observational cohort study was to assess the relationship between hemodynamic parameters evaluated via impedance cardiography (ICG) and echocardiographic parameters reflecting left ventricular function in 54 patients newly diagnosed with CD. The parameters assessed via ICG included stroke volume index (SI), cardiac index (CI), acceleration index (ACI), velocity index (VI), systemic vascular resistance index (SVRI), total artery compliance index (TACI). The echocardiographic parameters included left ventricular mass index (LVMI) and left ventricular systolic and diastolic parameters. Higher LVMI values were associated with lower SI (p = 0.003), CI (p = 0.001), VI (p = 0.048), TACI (p < 0.001), and with higher SVRI (p < 0.001). Poorer parameters of left ventricular diastolic function corresponded to the parameters assessed via ICG: (1) lower ratio E/A was associated with lower SI (p = 0.002), VI (p = 0.001), ACI (p = 0.01), TACI (p = 0.001); (2) lower average e’ was associated with lower SI (p = 0.017), CI (p = 0.009), VI (p = 0.004), TACI (p = 0.001), and with higher SVRI (p = 0.002); (3) higher ratio E/e’ corresponded to lower TACI (p = 0.01). Decreased global longitudinal strain corresponded to lower TACI (p = 0.046). CD is associated with impaired pumping function of the heart and higher afterload.